Presumed Guilty - Turow, Scott (New York : Grand Central Publishing, 2025)
"After Rusty Sabich's heated acquittal in the trial for his life, he's restlessly tried to accept his retirement and get his name out of the spotlight. Now, years later, he's found himself living a quiet life in the town of Mirror with a house on the idyllic lake and a new love, Bea. But the peace that's taken him so long to find comes crashing down when Bea's adoptive son, Aaron, who's under Rusty and Bea's supervision while on probation for a possession conviction, goes missing. The court has ordered that Aaron stay in contact with Rusty and Bea, and if he doesn't return soon, he might get sent back to jail. The trouble doesn't end when Aaron eventually turns up. It turns out that he'd been camping with Mae, his childhood sweetheart who has been an endless source of trouble for Aaron. Except Mae didn't return with Aaron. Mae's prosecuting attorney father, Hardy, brings in all of his resources from local police to the FBI to find his daughter. And when Mae is discovered dead, Hardy immediately points the finger at Aaron and the state jumps to trial. Rusty finds himself coming out of retirement to defend his step-son-to-be from a murder charge where the evidence doesn't seem to add up. But regardless of where the truth is pointing, it seems that the odds are stacked against Aaron. It's going to take all of Rusty's knowledge as a lawyer and judge to show the jury that Aaron isn't a murderer and that if they have any reasonable doubt, they must cast "Not guilty." Aaron's life is on the line and so is the one that Rusty has worked so hard for and all that stands between freedom for both of them is the rage-fueled prejudice against Aaron"--
Keywords: Detective and mystery fiction; Legal fiction (Literature).; Novels